ANALISIS PENGARUH DANA PIHAK KETIGA, LDR, NPL, CAR, ROA, DAN BOPO TERHADAP JUMLAH PENYALURAN KREDIT (Studi pada Bank Umum yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2009-2012) - Febrianto, Dwi Fajar; Muid, Dul (Diponegoro Journal of Accounting, 2013)
Banks have a major role in the economy, it is not separated from the role of the banks as an intermediary institution. The bank has a duty to collect funds from the public who and then channeled back ini the form of credit. The lending is not optimal conducted by banks into backgraound of this research. For that to know the influence of third-party funds, loan to deposit ratio (LDR), non performing loan (NPL), capital adequacy ratio (CAR), return on assets (ROA), and operating expenses to operating income ratio (BOPO) to total of loans. The population used in this study is a commercial bank listed on the Indonesia Stock Exchange (BEI) in the period 2009-2012. By using purposive sampling method, it is obtained as many as 24 banks as the study sample. The method of analysis used in this study is multiple linier regression. In this research also include the classical assumption that normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test. Results of this study indicate that the third-party funds and loan to deposit ratio (LDR) significant positive effect to total of loans. While non performing loan (NPL), capital adequacy ratio (CAR), return on assets (ROA), and operating expenses to operating income (BOPO) are not significant effect to total of loans.